Rail Vehicle Technology - Ihme, Joachim; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2022)
This textbook covers the theoretical principles and technology of railway and tramway vehicles. In addition to the legal principles, driving resistances, drives, brakes, running dynamics and running gears as well as the supporting structures and superstructures are dealt with. Great importance is attached to clear illustrations and numerous examples. With the help of this book, even engineers and railway enthusiasts from other disciplines can successfully familiarize themselves with the field of railway vehicle technology. The present edition has been revised and supplemented by the chapter "Engineering in rail vehicle construction". The contents Introduction - Driving resistances of rail vehicles - Driving machines, power transmission - Brakes for rail vehicles - Wheelset guidance, suspension, damping - Structures and superstructures of rail vehicles - Engineering in rail vehicle construction. The target groups - Students of mechanical engineering and electrical engineering - Engineers who need to familiarize themselves with the field of rail vehicles The author Dr. Joachim Ihme is a lecturer in rail vehicle technology at Ostfalia HaW (formerly Braunschweig/Wolfenbüttel University of Applied Sciences). Until the end of 2015, he was a professor at this university specializing in machine elements, strength of materials, logistics and rail vehicles. His university activities were preceded by several years of employment with a rail vehicle manufacturer. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Introduction -- Driving resistances of rail vehicles -- Driving machines, power transmission -- Brakes for rail vehicles -- Wheelset guidance, suspension, damping -- Supporting structures and superstructures of rail vehicles -- Engineering in rail vehicle construction.
Keywords: Transportation engineering; Traffic engineering; Transportation Technology and Traffic Engineering; Railroad engineering; Railroad trains; Street-railroads; Railroad cars